Osteomalacia: The Missing Link in the Pathogenesis of Bisphosphonate‐Related Osteonecrosis of the Jaws? - Bedogni, Alberto; Saia, Giorgia; Bettini, Giordana; Tronchet, Anita; Totola, Andrea; Bedogni, Giorgio; Tregnago, Paolo; Valenti, Maria Teresa; Bertoldo, Francesco; Ferronato, Giuseppe; Nocini, Pier Francesco; Blandamura, Stella; et al. (The oncologist (Dayton, Ohio), 2012)
Background. Bisphosphonate‐related osteonecrosis of the jaw (BRONJ) is a well‐documented adverse event from treatment with nitrogen‐containing bisphosphonates (NBPs). During a preliminary histomorphometric study aimed at assessing the rate of bone remodeling in the jaws of patients with surgically resected BRONJ, we found a defect of bone mineralization (unpublished data). We hypothesized that osteomalacia could be a risk factor for BRONJ in patients taking NBPs. Therefore, we looked for static and dynamic histomorphometric evidence of osteomalacia in biopsies from subjects with and without BRONJ. Methods. This case‐control study used histomorphometric analysis of bone specimens of patients using NBPs (22 patients with BRONJ and 21 patients without BRONJ) who required oral surgical interventions for the treatment/prevention of osteonecrosis. Patients were given tetracycline hydrochloride according to a standardized protocol before taking bone biopsies from their jaws. Biopsies with evidence of osteomyelitis or necrosis at histology were excluded from the study. Osteomalacia was defined as a mineralization lag time >100 days, a corrected mean osteoid thickness >12.5 mm, and an osteoid volume >10%. Results. In all, 77% of patients with BRONJ were osteomalacic compared with 5% of patients without BRONJ, according to histomorphometry. Because osteomalacia was found almost exclusively in NBP users with BRONJ, this is likely to be a generalized process in which the use of NBPs further deteriorates mechanisms of bone repair. Conclusions. Osteomalacia represents a new and previously unreported risk factor for disease development. This finding may contribute to a better understanding of the pathogenesis of this disease and help with the development of strategies to increase the safety of NBP administration. This case‐control study uses histomorphometric analysis of bone specimens to determine whether osteomalacia is a risk factor for bisphosphonate‐related osteonecrosis of the jaw in patients taking nitrogen‐containing bisphosphonates.